Comparison between Elderly Attenders and Non-Attenders of Pusat Aktiviti Warga Emas in Sarawak - Izzaty, Hamidi; Jeffery, Stephen; Noorzilawati, Sahak (Secholian Publication, 2023)
Malaysia is not left behind as it is going towards becoming an aging nation. Currently, there are 10.7% of the population who are above 60 years old which is equivalent to 3.5 million of elderly people and this is expected to rise in the near future. The objective of this research is to compare the quality of life, activities of daily living, cognitive function and depression between elderly attenders and non-attenders of Pusat Aktiviti Warga Emas (PAWE). In this cross-sectional study, a total of 735 elderly participated where 101 elderly who attended PAWE and the remaining 634 elderly did not attend PAWE. Older People’s Quality of Life (OPQOL), Prospective Retrospective Memory Questionnaire (PRMQ), Geriatric Depression Scale (GDS), Katz Activities of Daily Living and Lawton Instrumental Activities of Daily Living were used as study instruments. The statistical analysis involved were Pearson’s correlation, independent t-test, Partial Least Square Structural Equation Modeling (PLS-SEM) and multiple group analysis. Household income and activities of daily living have shown positive correlation with quality of life. Cognitive function and depression correlated negatively with quality of life. Based on PLS-SEM, there was better quality of life, activities of daily living, cognitive function, and lesser depressive symptoms among elderly PAWE attenders. The findings obtained from this study will be able to support the planning and future programs of expanding senior activity centres such as PAWE as it promotes healthy ageing among elderly people.